Posterior tibial nerve stimulation for overactive bladder—techniques and efficacy - Bhide, Alka A. (Int Urogynecol J, 2019)
The ideal treatment for overactive bladder is still elusive. In those where medication fails to improve symptoms options include invasive treatments such as botulinum toxin-A, sacral neural stimulation or posterior tibial nerve stimulation. Scientific professional society guidelines advise percutaneous posterior tibial nerve stimulation as a third line treatment option only after multi-disciplinary team review as well as failure of both conservative and pharmacological management. The aim of this article is to review all techniques for tibial nerve stimulation and their efficacy.